The Role of Education in Prevention of Suicide Terrorism - Krstić, Marko (Zbornik Instituta za kriminološka i sociološka istraživanja, 2018)
The work will identify the importance of education on the prevailing situation of suicidal terrorism and combativeness. A nation that develops on a solid foundation of the education system has a futuristic, long-term goal. Some countries lack an effective education that can focus them on and focus on one goal and unite them as a unique and compact nation. The emphasis is placed on the common understanding and importance of education, and then the need for dialogue and discussion that form the views of ordinary people about the destruction caused by terrorism, and the impact of intimidation on the suppression of acts of terrorists. The psychological profiling of suicide bombers has not always been successful, and scientists agree that the approach to the study of this phenomenon should be changed and emphasis on the process of recruitment and training of suicide bombers and the selection of individuals to take on leadership roles in terrorist organizations, which would certainly constitute an effective tool in fighting this kind of terrorism in the future. Education is the only weapon for a courageous fight against terrorists, because terrorism can not be defeated by firearms, and that line must be understood in time. The best way to combat terrorism is to spread and foster education and upbringing. Education opens people's minds; it helps them understand and carry out drastic changes.